Modeling Lymphocytes - Wittmann, Jürgen (Systems Medicine, 2020)
Our immune system is continuously attacked by billions of invaders or is exposed to foreign substances. Only joint forces of various cell types, tissues and organs help to protect the body successfully against attacks from these outsiders. Endogenous threats like continuously arising, nascent transformed cells in the body also need to be recognized and eliminated. Sometimes, responses of the immune system also go awry, as in allergy, autoimmune diseases or in primary or acquired immunodeficiency disorders, leaving people more susceptible to infections due to a not properly or a not at all working immune system. The immune system is however able to cope with these manifold threats using a complex array of cellular and molecular processes. Modeling approaches have already helped achieving greater understanding of biological processes by both generating models that formalize biological ideas and by extracting information from experiments that might not be obvious or intuitive from the biological approach. Predictions and hypotheses arising from application of the models can then be tested experimentally, leading to a continuous iteration of refining the model and testing the novel predictions. To appreciate the multifaceted possibilities for modeling approaches in lymphocyte development, I first give a primer on immunology by introducing key players of the immune system and how these are generated, activated and regulated. Subsequently, I shortly discuss some cases where modeling has already helped experimental immunologists in understanding their data and offering new experimentally testable hypotheses to deepen our understanding of processes during an immune reaction.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Adaptive immunity; Affinity maturation; B cell development; B cells; B-cell receptor; CD4; CD8; Germinal center reaction; Innate immunity; Lymphocyte modeling; T cell activation; T cell development; T-cell receptor